2021
DOI: 10.3389/fphys.2021.505149
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise Recovery Methods Focus on Young Soccer Players: A Systematic Review

Abstract: Background: Prescription of post-match or post-training recovery strategies in young soccer players is a key point to optimize soccer performance. Considering that the effectiveness of recovery strategies may present interindividual variability, scientific evidence-based recovery methods and protocols used in adults are possibly not applicable to young soccer players. Therefore, the current systematic review primarily aimed to present a critical appraisal and summary of the original research articles that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…In this sense, the elevation of CK, LDH and DOMS values observed immediately after the match (0 h) in both categories was, in a way expected, once the soccer match is able to generate physical and physiological wear in players, as these markers tend to remain elevated immediately after the soccer match [12,13]. Studies involving young soccer players that investigated blood markers of muscle damage and DOMS beyond time 0 h found that the blood marker of muscle damage remained elevated between 24 h [18,36] and up to 72 hours after the soccer match [19].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this sense, the elevation of CK, LDH and DOMS values observed immediately after the match (0 h) in both categories was, in a way expected, once the soccer match is able to generate physical and physiological wear in players, as these markers tend to remain elevated immediately after the soccer match [12,13]. Studies involving young soccer players that investigated blood markers of muscle damage and DOMS beyond time 0 h found that the blood marker of muscle damage remained elevated between 24 h [18,36] and up to 72 hours after the soccer match [19].…”
Section: Discussionmentioning
confidence: 65%
“…Several sports scientists and training professionals have thus focused on the response of indicators such as CK, LDH, and delayed onset muscle soreness (DOMS) to measure the physical wear generated by a match in athletes [12,13]. This is because the extravasation of CK and LDH enzymes into the bloodstream occurs mainly due to a series of cellular and tissue micro damages generated by the mechanical action of high-intensity muscle contraction, as well as by the frequent physical contacts suffered by athletes during matches [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“… Taking into consideration how physiological stress and physiological and biochemical markers are affected when the same players start in sequential matches and how they differ from those who remain on the bench ( 67 , 68 ). Using individualized protocols based on the players' characteristics such as actual fitness level, injury history and preferences ( 66 , 69 ). Educating players to take responsibility for their recovery.…”
Section: Practical Applications To Increase Player Availabilitymentioning
confidence: 99%
“…Using individualized protocols based on the players' characteristics such as actual fitness level, injury history and preferences ( 66 , 69 ).…”
Section: Practical Applications To Increase Player Availabilitymentioning
confidence: 99%
“…During a season, the chances of cramps are very high due to stressful training and games. As a result, there is a lot of emphasis on postexercise and competition recovery (4).…”
Section: Introductionmentioning
confidence: 99%